Peningkatan Kinerja Guru melalui Supervisi Klinis di SD Negeri 1 Moyot Tahun Pelajaran 2022/2023 - Harmain, Harmain (YASIN, 2023)
The type of research conducted was school action research where the target was teachers at SDN 1 Moyot, Sakra sub-district. The purpose of this classroom action research (CAR) is to find out the extent to which teacher competency increases in high-class learning by applying clinical supervision. In school action research (PTS) this was carried out in 2 cycles, the results of the actions taken proved to be able to increase teacher competence by achieving classical completeness, namely 88.33%. Classical completeness of 69.30% obtained in cycle I can increase in cycle II to 83.33%. In terms of teacher activity in learning, that is, in cycle I, the moderately active category was obtained, increasing to an active category. The results of this action research show that the application of clinical supervision can improve teacher performance with mastery reaching 83.33%.